2002
DOI: 10.1007/s00705-002-0818-2
|View full text |Cite
|
Sign up to set email alerts
|

Avian paramyxoviruses and influenza viruses isolated from mallard ducks (Anas platyrhynchos) in New Zealand

Abstract: A comprehensive study using virological and serological approaches was carried out to determine the status of live healthy mallard ducks (Anas platyrhynchos) in New Zealand for infections with avian paramyxoviruses (APMV) and influenza viruses (AIV). Thirty-three viruses isolated from 321 tracheal and cloacal swabs were characterized as: 6 AIV (two H5N2 and four H4N6), 10 APMV-1 and 17 APMV-4. Of 335 sera samples tested for AIV antibodies, 109 (32.5%) sera were positive by nucleoprotein-blocking ELISA (NP-B-EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 32 publications
3
36
0
3
Order By: Relevance
“…During the wild bird surveillance program for AI in Korea, a variety of haemagglutinating viruses were isolated and identified as AIV, APMV type 1, 4 and 6 and their prevalence was comparable to other reports Fujimoto et al, 2010;Hanson et al, 2005;Hinshaw et al, 1985;Hlinak et al, 2006;Shortridge et al, 1980;Stalknecht et al, 1991;Stanislawek et al, 2002;Tumova, 2003). In addition, there was evidence of co-infection found in 15 viruses in this study, which were reported in the other studies including coinfected isolates with different subtypes of AIVs (Sharp et al, 1997), with AIV and APMV type 1 (Dormitorio, 2009) , Table 3 However, there has been little information on the epidemio-logy of APMVs other than APMV type 1 in Korea.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…During the wild bird surveillance program for AI in Korea, a variety of haemagglutinating viruses were isolated and identified as AIV, APMV type 1, 4 and 6 and their prevalence was comparable to other reports Fujimoto et al, 2010;Hanson et al, 2005;Hinshaw et al, 1985;Hlinak et al, 2006;Shortridge et al, 1980;Stalknecht et al, 1991;Stanislawek et al, 2002;Tumova, 2003). In addition, there was evidence of co-infection found in 15 viruses in this study, which were reported in the other studies including coinfected isolates with different subtypes of AIVs (Sharp et al, 1997), with AIV and APMV type 1 (Dormitorio, 2009) , Table 3 However, there has been little information on the epidemio-logy of APMVs other than APMV type 1 in Korea.…”
Section: Discussionsupporting
confidence: 82%
“…Surveillance programs on different APMV serotypes have been conducted worldwide on poultry farms, wild populations or both (Alkhalaf, 2009;Maldonado et al, 1994;Maldonado et al, 1995;Stanislawek et al, 2002;Warke et al, 2008a;Zhang et al, 2007). These investigations have been directed at prevalence in order to understand the status of infection in wild birds and domestic flocks and to better understand the role of wild birds in spreading the viruses or infecting domestic birds with the viruses (Hinshaw et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It was observed the occurrence of serotype 4 (APMV-4) in free-living birds, such as duck (Alexander et al, 1979;Gough & Alexander, 1984;Stallknecht et al;Maldonado et al, 1995;Stanislawek et al, 2002;Jeon et al, 2008;Rosseel et al, 2011), goose and coot (Maldonado et al) and the serotype 5 (APMV-5) in parakeet, leading to depression, dyspnea, torticollis, vomiting, diarrhea and death (Mustaffabab Jee, 1974;Nerome et al, 1978;Gough et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The serotypes 6 (APMV-6) and 7 (APMV-7) were isolated from healthy free-living birds such as duck Maldonado et al;Stanislawek et al;Warke et al, 2008;Rosseel et al), goose, grey heron, blackheaded gull, coot, spoonbill, house sparrow (Maldonado et al), turkey with respiratory disease associated to egg production drop (Saif et al, 1997) and ostrich with enteritis (Wollcook et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…그 러나 최근 국가 간 지역 간 이동이 자유로운 야생 조류의 경 우, 우리나라와 중국에서 NDV 분리 사례들이 보고 (Cai et al, 2011;Choi et al, 2008a;Kim et al, 2011;Lee et al, 2009;Shim et al, 2011;Zhu et al, 2010) Order (Kim et al, 2007;.Kim et al, 2011;Jindal et al, 2009;Stanislawek et al, 2002;Takakuwa et al, 1998;Zanetti et al, 2005)되고 있 기 때문에 지역 간 NDV의 확산을 매개하는 중요한 요인으 로 작용할 수 있다. 이들 야생 조류에서 분리되는 NDV는 대부분 약독형 NDV이지만, 강독형 NDV도 분리되는 사례 (Choi et al, 2008a;Majiyabe & Nawathe, 1981;Takakuwa et al, 1998;Wobeser et al, 1993;Zhu et al, 2010)가 있다.…”
unclassified